2004
DOI: 10.1128/mcb.24.7.2710-2719.2004
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Sensitive K+ Channels Regulate the Concentrative Adenosine Transporter CNT2 following Activation by A1 Adenosine Receptors

Abstract: This study describes a novel mechanism of regulation of the high-affinity Na ؉ -dependent adenosine transporter (CNT2) via the activation of A 1 adenosine receptors (A 1 R). This regulation is mediated by the activation of ATP-sensitive K ؉ (K ATP ) channels. The high-affinity Na ؉ -dependent adenosine transporter CNT2 and A 1 R are coexpressed in the basolateral domain of the rat hepatocyte plasma membrane and are colocalized in the rat hepatoma cell line FAO. The transient increase in CNT2-mediated transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 48 publications
4
53
1
2
Order By: Relevance
“…Its function in liver is regulated by purinergic activation of A1R through a mechanism in which K ATP channels are implicated (Duflot et al, 2004). This was the first indirect evidence in support of the putative interaction between adenosine transport and the energy status of the cell.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Its function in liver is regulated by purinergic activation of A1R through a mechanism in which K ATP channels are implicated (Duflot et al, 2004). This was the first indirect evidence in support of the putative interaction between adenosine transport and the energy status of the cell.…”
Section: Discussionmentioning
confidence: 85%
“…This makes CNT2 a better candidate to mediate adenosine transport and thereby contribute to the intracellular AMP pool, although a role for ENT1 cannot be ruled out. Moreover, we have recently demonstrated that CNT2 function can be transiently stimulated by purinergic activation of A1 receptors, through a mechanism that is mediated by K ATP channel opening (Duflot et al, 2004). Since this particular type of K + channel is indeed a sensor of changes in the adenosine nucleotide pool, as is AMPK, extracellular adenosine, and in particular its uptake through CNT2, might contribute to AMPK regulation.…”
Section: Introductionmentioning
confidence: 99%
“…The preconditioning effect in the liver has been mainly described as being mediated through the A2 receptors, although recent studies report some presence of A1 receptors in the liver (17). If we carefully study the sinusoidal cell damage at the time reperfusion, and the hepatocellular damage at five days, we can surprisingly see a certain beneficial effect despite this selective blocking of the A1-type receptors.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, adenosine could exert its effect by counteracting its receptors. Until now, only A2 receptors have been clearly demonstrated to be involved in the preconditioning effect in the liver; however the presence of the other A1 subtype has been proven in hepatocytes as well (17).…”
Section: Introductionmentioning
confidence: 99%
“…Insulin regulates adenosine transport through different signaling pathways that involve PI3K, MAPK, NO synthase, PKC and MAP kinase [64][65][66] . One study showed that adenosine transport is up-regulated by activation of the A1 adenosine receptor through ATP-sensitive K-channels in hepatocytes, suggesting some positive feedback regulation among adenosine receptors and the adenosine transporter [67] . The effects of proliferative (EGF and TGF-a) and differentiating (glucocorticoid) hormones were demonstrated in IEC-6 cells (a rat intestinal cryptal cell line).…”
Section: Regulation Of Adenosine Transport and Cnt2 Expression In Genmentioning
confidence: 99%